On the growth of a class of entire Dirichlet series - Kulyavetc', L.V.; Mulyava, O.M. (Carpathian Mathematical Publications, 2014)
In terms of generalized orders it is investigated a relation between the growth of an entire Dirichlet series F(s)=_n=1^∞a_n{sλ_n} and the growth of entire Dirichlet series F_j(s)=_n=1^∞a_n, j{sλ_n}, 1j2, provided the coefficients a_n are connected with the coefficients a_n, j by some correlations.